Meningkatkan Keterampilan Hots (Higher Order Thinking Skills) Melalui Pendekatan Pembelajaran Berdiferensiasi Di Sekolah Dasar - Nadhilah Syafitri; Zuhti Atitta Putri; Ade Irma; Riski Fatma Sofi Nasution; Nadine Gwen C.H. Sitorus; Asna Istikmalatul Muktamaroh (Jurnal Keluarga Sehat Sejahtera, 2026)
This study aims to analyze the implementation of differentiated instruction in improving elementary school students’ Higher Order Thinking Skills (HOTS). HOTS are essential 21st-century skills because students are required to think critically, creatively, analyze information, and solve problems. This research employed a qualitative approach using the Systematic Literature Review (SLR) method. Data were collected through article searches on Google Scholar. using keywords related to differentiated instruction and HOTS. The analyzed articles were international journals published between 2017–2026 that met the research inclusion criteria. Based on the selection process, 10 international journals were analyzed using thematic analysis techniques. The findings showed that differentiated instruction effectively improves students’ critical thinking, creativity, problem-solving skills, and active participation in learning. Differentiated instruction also helps teachers adjust learning strategies according to students’ needs, interests, and abilities, making the learning process more flexible and meaningful. In addition, the successful implementation of differentiated instruction is influenced by teachers’ competencies in designing adaptive and student-centered learning. Therefore, differentiated instruction can be an effective strategy to support the development of HOTS among elementary school students.